Influence of sintering parameters on the compressive yield strength of stainless steel foams produced by the space holder method - Tan, Koon Tatt; Norhamidi Muhamad,; Andanastuti Muchtar,; Abu Bakar Sulong,; Neo, Ming Cherng (Penerbit Universiti Kebangsaan Malaysia, 2016)
Metallic foams are a new class of materials that have a great potential to be used in various functional and structural applications. Due to their competitive price compared to aluminium, metallic foams are anticipated to become an alternative material for light-weight structures. In this study, stainless steel foams are fabricated using a powder space holder method. The materials used include stainless steel powder, a novel space holder glycine and binders consisting of palm stearin and of polyethylene (PE). The stainless steel foams are sintered at 1100oC, 1200oC and 1300oC with sintering times of 1, 2 and 3 h, respectively, to investigate the effects of the sintering parameters on the compressive yield strength of the stainless steel foams. The results showed that all of the stainless steel foams produced exhibit the general behaviours of metal foams. The sintering time is the most significant parameter that influences the compressive yield strength of stainless steel foams. Increasing the sintering temperature and sintering time will increase the compressive yield strength. The interaction between the sintering temperature and sintering time is found to be not statistically significant.